Application of the Dietary Environmental Index to Model More Sustainable Versions of Food Intake Patterns Reported in the 2007–2008 NHANES (OR20-01-19). (13th June 2019) - El-Abbadi, Naglaa; Griffin, Timothy; Peters, Christian; Nelson, Miriam; Jacques, Paul
Abstract: Objectives: Constructing nutritionally replete as well as environmentally benign dietary patterns is at the core of diet sustainability efforts, yet these must also consider factors of personal preference and accessibility to be widely acceptable. This study aimed to model how observed food selection may be modified to optimize nutritional quality while mitigating environmental harm, using comparable food substitutions. Methods: Day 1 dietary intake reported by adult participants in the 2007–2008 NHANES was scored using the Dietary Environmental Index (DEX), a tool to assess life cycle environmental impacts standardized by diet quality, calculated as the ratio of a Nutrient Density Score (NDS) to Environmental Impact Score (EIS) for 7500 food products consumed in the United States. Low-scoring food products, based on their higher environmental impact and lower nutrient density, were directly substituted by a high-DEX alternative food from within the same What We Eat In America food category. Resultant changes to overall food group and nutrient levels were assessed. Results: Food group composition of the DEX-modeled daily food intake patterns shifted towards lower quantities of red meat, and higher quantities of poultry, legumes, whole grains, and vegetables. Levels of beneficial nutrients to encourage, such as fiber and select vitamins and minerals, increased by 15–81% in the DEX-models, while protein levels stayed about the same. Nutrients to limit, including saturated fat, sodium, and added sugar, decreased by 12–16%. Individual direct environmental impacts related to climate change, land use, water depletion, and marine eutrophication improved by 11–17% in the DEX-models. Conclusions: Findings demonstrate the potential nutritional as well as environmental benefits of relatively simple food substitutions within an existing diet pattern, in a manner aimed to be palatable to the individual. Funding Sources: The National Institute of Food and Agriculture, US Department of Agriculture and the Agricultural Research Service.